Modulation of neural activity by angle of rotation during imagined spatial transformations - Keehner, Madeleine; Guerin, S.; Miller, M.; Turk, D.; Hegarty, M. (2006)
Imagined spatial transformations of objects (e.g., mental rotation) and the self (e.g., perspective taking) are psychologically dissociable. In mental rotation, the viewer transforms the location or orientation of an object relative to stable egocentric and environmental reference frames. In imagined shifts of perspective, the viewer's egocentric reference frame is transformed with respect to stable objects and environment. Using fMRI we showed that during mental transformations of objects the right superior parietal cortex exhibited a positive linear relationship between hemodynamic response and degrees of rotation. By contrast, during imagined transformations of the self, the same regions exhibited a negative linear trend. We interpret this finding in terms of the role of parietal cortex in coding the locations of objects in relation to the body.